Renal Cell Carcinoma Metastases to the Pancreas: Value of Arterial Phase Imaging at MDCT. (April 2013) - Corwin, Michael T; Lamba, Ramit; Wilson, Machelle; Mcgahan, John P
Background: The pancreas is an increasingly recognized site of renal cell carcinoma metastases. It is important to determine the optimal MDCT protocol to best detect RCC metastases to the pancreas. Purpose: To compare the rate of detection of renal cell carcinoma metastases to the pancreas between arterial and portal venous phase MDCT. Material and Methods: A retrospective review of CTs of the abdomen yielded six patients with metastatic RCC to the pancreas. Five of six patients had pathologically proven clear cell RCC. Two blinded reviewers independently reported the number of pancreatic lesions seen in arterial and venous phases. Each lesion was graded as definite or possible. The number of lesions was determined by consensus review of both phases. Attenuation values were obtained for metastatic lesions and adjacent normal pancreas in both phases. Results: There were a total of 24 metastatic lesions to the pancreas. Reviewer 1 identified 20/24 (83.3%) lesions on the arterial phase images and 13/24 (54.2%) lesions on the venous phase. Seventeen of 20 (85.0%) arterial lesions were deemed definite and 9/13 (69.2%) venous lesions were definite. Reviewer 2 identified 19/24 (79.2%) lesions on the arterial phase and 14/24 (58.3%) on the venous phase. Seventeen of 19 (89.5%) arterial lesions were definite and 7/14 (50%) venous lesions were definite. Mean attenuation differential between lesion and pancreas was 114 HU and 39 HU for arterial and venous phases, respectively (P < 0.0001). Conclusion: Detection of RCC metastases to the pancreas at MDCT is improved using arterial phase imaging compared to portal venous phase imaging.